A pilot study investigating the association between chronic bilateral vestibulopathy and components of a clinical functional assessment tool. (3rd June 2017) - Swanenburg, Jaap; Zurbrugg, Aron; Straumann, Dominik; Hegemann, Stefan C. A.; Palla, Antonella; de Bruin, Eling D.
ABSTRACT: Background : This study aimed to analyze the association between prospectively assessed falls and functional abilities in patients with bilateral vestibulopathy (BVP). Methods : Nineteen BVP patients had functional abilities assessed at baseline with the expanded timed get-up-and-go (ETGUG) test. Falls were prospectively recorded with a monthly "fall calendar" over a one-year period. Association between baseline functional abilities and falls was evaluated by Mann–Whitney U testing. Logistic regression was applied to describe the relationship between falls and functional abilities. Area under the receiver-operating characteristic curve (AUC) was used predicting falls based on gait speed. Results : Eight (45%) of 18 patients (61.11 ± 15.19 years, 12 male) reported 19 falls. Fallers had a significantly faster preferred gait speed ( p = 0.03) in the fifth component of the ETGUG. Preferred gait speed was a significant factor in the prediction of falls model (odds ratio = 2.00, p = 0.05, CI = 1.00/4.00 per 10 cm/s). ACU was 0.80 and the cutoff score of 1.35m/s (sensitivity = 75%, specificity = 70%) in predicting falls. Discussion : BVP patients classified as fallers demonstrated significant faster gait speed after a turning maneuver. Future studies in larger BVP patient samples are needed to refute or confirm our findings.